2022
DOI: 10.1080/17482631.2022.2092958
|View full text |Cite
|
Sign up to set email alerts
|

Care coordination, consistency and continuity: the case of the key worker role in children’s cancer care

Abstract: Purpose The overall aim was to evaluate the key worker role across principal treatment centres for children with cancer in England, Wales and Scotland. Methods Mixed-methods case study gathering data from multiple perspectives using questionnaires, interviews, focus groups and reports/performance documents over a two-year period. Framework approach was adopted to analyse transcripts and documentary data. Results Participants included: 22 nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The implementation of successful projects in this area regarding complex chronic diseases in pediatrics is also described, with the role of case managers generating gains compatible with those found in this review [ 33 , 34 , 158 , 159 ]. However, there is also evidence of the inherent difficulties associated with the turnover of professionals in the inpatient setting, their potential overload and the high emotional demand [ 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of successful projects in this area regarding complex chronic diseases in pediatrics is also described, with the role of case managers generating gains compatible with those found in this review [ 33 , 34 , 158 , 159 ]. However, there is also evidence of the inherent difficulties associated with the turnover of professionals in the inpatient setting, their potential overload and the high emotional demand [ 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in clinical care practice for intravenous home chemotherapy interventions in the current study are identified by the workshop HCPs as barriers in two main topics: 1) "Increased educational support as part of care", and 2) "Increased care coordination", indicating potential key uncertainties to be cognizant of when testing feasibility of the intervention and as relevant evaluation outcome measures [29][30][31]. Martins et al identify "care coordination" as one of three core elements of the critical worker's care process in a comprehensive study that explores and defines the role of the nurse specialist in UK [54,55]. Although care coordination in these studies is explored within a context whereby shared care centers are well-established in the pediatric cancer care, it underlines the family need for care coordination and elucidates some of the challenges to be attentive to when complex care is transferred to the home.…”
Section: Discussionmentioning
confidence: 99%